Improvement of thermal performance of generator step-up transformers. (5th March 2015) - Sitar, Robert; Janić, Žarko; Štih, Željko
Abstract: Generator step-up transformers have high losses in structural parts due to high current leads. As distribution of magnetic field is nonuniform it may easily cause high local losses and high temperature rises. This paper studies impact of aluminum shields on losses and temperature rise. Using a 3D finite element method (FEM) software, calculations for five different leads arrangement are done on a model of a 220 MVA transformer with phase current of 4.4 kA. Influence on results of non-linear magnetic property and non-linear thermal parameters are studied as well. Finally, calculation results are verified by measurements. Experiment has confirmed that aluminum shield is a correct measure for reducing tank local overheating. Highlights: 3D transformer model for coupled electromagnetic–thermal calculation is presented. Effect of aluminum shield on tank temperature is examined. On all lead arrangements aluminum shield reduces temperature but not total losses. Calculation method is verified with an experiment made on a real power transformer.